2019
DOI: 10.1111/mmi.14183
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering nisin to overcome the nisin resistance protein

Abstract: Summary The emergence and dissemination of antibiotic resistant bacteria is a major medical challenge. Lantibiotics are highly modified bacterially produced antimicrobial peptides that have attracted considerable interest as alternatives or adjuncts to existing antibiotics. Nisin, the most widely studied and commercially exploited lantibiotic, exhibits high efficacy against many pathogens. However, some clinically relevant bacteria express highly specific membrane‐associated nisin resistance proteins. One nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 60 publications
4
45
0
Order By: Relevance
“…The nisin resistance protein (NSR) is a protease which cleaves nisin A at Ser29, significantly reducing the activity of the peptide. Employing a bioengineering strategy, Field et al (37) demonstrated that the substitution of residues 29 and 30 with proline and valine, respectively (derivative designated S29PV), rendered the peptide resistant to proteolytic digestion by NSR. In this study, we found that the nisin J producer displays a higher resistance to NSR proteolytic enzymes than does nisin A, which is possibly due to a glycine residue at position 30 instead of the isoleucine as found in nisin A. Interestingly, a study carried out by Simões et al (38) involving a multidrugresistant S. capitis clone, NRCS-A, a major pathogen involved in sepsis in preterm neonates, demonstrated the presence of an NSR-encoding gene.…”
Section: Discussionmentioning
confidence: 99%
“…The nisin resistance protein (NSR) is a protease which cleaves nisin A at Ser29, significantly reducing the activity of the peptide. Employing a bioengineering strategy, Field et al (37) demonstrated that the substitution of residues 29 and 30 with proline and valine, respectively (derivative designated S29PV), rendered the peptide resistant to proteolytic digestion by NSR. In this study, we found that the nisin J producer displays a higher resistance to NSR proteolytic enzymes than does nisin A, which is possibly due to a glycine residue at position 30 instead of the isoleucine as found in nisin A. Interestingly, a study carried out by Simões et al (38) involving a multidrugresistant S. capitis clone, NRCS-A, a major pathogen involved in sepsis in preterm neonates, demonstrated the presence of an NSR-encoding gene.…”
Section: Discussionmentioning
confidence: 99%
“…Induction experiments were performed using L. lactis NZ9000 pNZ8150 gfp+, where gfp acts as a reporter of expression from a nisin A inducible promoter 54 . An overnight culture of this strain was diluted 1:100 into fresh media and incubated until the OD 600 reached 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Nisin (3.5 kDa) is produced by some Lactococcus lactis subsp. lactis strains and, as a protein compound, comprises 34 amino acid residues [8]. Its antimicrobial properties consist of permeabilization of the bacterial cell membrane by pore formation, leading to leakage of cellular content and disruption of the cell, preventing growth [9].…”
Section: Introductionmentioning
confidence: 99%